Proceedings of the XII International Symposium on Biological Control of Weeds, La Grande Motte, France, 22-27 April, 2007 2008
DOI: 10.1079/9781845935061.0182
|View full text |Cite
|
Sign up to set email alerts
|

Diclidophlebia smithi (Hemiptera: Psyllidae) a potential biological agent for Miconia calvescens .

Abstract: Diclidophlebia smithi Burckhardt, Morais and Picanço (Hemiptera: Psyllidae) is a monophagous species which was selected as possible agent of biological control of miconia, Miconia calvescens DC. (Melastomataceae), a native plant of Central and South America that has become an aggressive invader of forest ecosystems in French Polynesia, Hawaii and Australia. The objective of this work was to study the biology and population dynamics of D. smithi in Viçosa and Dionísio (state of Minas Gerais, Brazil) from June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…To select agents for the biological control of M. calvescens , surveys on the arthropods that attack this weed in Brazil have been carried out since 2001 (Picanço et al 2005; Morais et al 2010a, 2010b). In these previous studies, some species of Lepidoptera were found damaging M. calvescens , including Salbia lotanalis Druce (Lepidoptera: Pyralidae) (mistakenly identified as Ategumia sp.…”
Section: Introductionmentioning
confidence: 99%
“…To select agents for the biological control of M. calvescens , surveys on the arthropods that attack this weed in Brazil have been carried out since 2001 (Picanço et al 2005; Morais et al 2010a, 2010b). In these previous studies, some species of Lepidoptera were found damaging M. calvescens , including Salbia lotanalis Druce (Lepidoptera: Pyralidae) (mistakenly identified as Ategumia sp.…”
Section: Introductionmentioning
confidence: 99%
“…Several insects from Brazil and Costa Rica have been studied as potential biological control agents of M. calvescens (Burckhardt et al 2005(Burckhardt et al ,2006Picampo et al 2005;Badenes-Perez and Johnson 2007a,b, 2008, Allen 2010, Badenes-Perez et al 2010, Morais et al 2010a,b, Reichert et al 2010, Chacon-Madrigal et al 2012, Morais et al 2012). Among these insects, Salbia lotanalis Druce (Lepidoptera: Crambidae) has been studied in its native habitat in Brazil and in Costa Rica (Castillo 2009;Morais et al 2010bMorais et al , 2012Janzen and Hallwachs 2014;Badenes-Perez et al 2014).…”
mentioning
confidence: 97%
“…As a result of M. luteofascia feeding, seed germination was drastically reduced from 34.8% in undamaged fruits to 1.9 and 0.1% in fruits with medium and high fruit damage, respectively. Through impacts on reproduction of M. calvescens, M. luteofascia might prove a useful complement to the effects of a number of potential biological control agents under evaluation (Burckhardt et al 2005;Johnson 2007a,b, 2008;Allen 2010;Badenes-Pérez et al 2010Hanson et al 2010;Morais et al 2010aMorais et al ,b, 2012Morais et al , 2013Nishida 2010;Reichert et al 2010;Castillo et al 2014).…”
mentioning
confidence: 99%